Effect of Lubricant Contamination on EHL Rolling Contact: Response Surface Methodology - MAATALLAH, Sabrina; SARI, Mohamed Rafik; KHOCHEMANE, Lakhdar (Engineering Transactions, 2016)
In this research the failure of EHL rolling contact in highly contaminated media is investigated. The conducted study uses an original experimental device to predict the effects of operating parameters, namely, surface hardness, contaminant concentration, rotational velocity, and the applied load on wear and roughness components. The planning of the experiments was based on Taguchi’s L9 orthogonal array. The statistical significance of the above mentioned parameters on the results was explored using the analysis of variance (ANOVA). The relationship between responses’ factors and the operating parameters is also established employing the multiple linear regression method. ANOVA results show clearly that the surface hardness (H) and contaminant concentration (C) are the most significant factors that influence wear and surface roughness of machine elements.